Small Cell Lung Cancer: Advances in Diagnosis and Management - Chauhan, Ayushi F.; Liu, Stephen V. (Seminars in Respiratory and Critical Care Medicine, 2020)
Small cell lung cancer (SCLC) is an aggressive subtype of lung cancer characterized by rapid growth and early spread. It is a highly lethal disease that typically is diagnosed at a late stage. Surgery plays a very small role in this cancer, and management typically involves chemotherapy, delivered with thoracic radiation in early-stage disease. Platinum-based chemotherapy is initially very effective, inducing rapid and often deep responses. These responses, though, are transient, and upon relapse, SCLC is highly refractory to therapy. Immunotherapy has shown promise in delivering meaningful, durable responses and the addition of immunotherapy to first-line chemotherapy has led to the first improvements in survival in decades. Still, the disease remains difficult to manage. Incorporating radiation therapy at specific points in patient management may improve disease control. The development of predictive biomarkers and novel targeted therapies will hopefully improve options for patients in the near future. This review focuses on the current standards of care and future directions.
Keywords: small cell lung cancer; immunotherapy; chemotherapy; targeted therapy; review